From Praśasti to Political Culture: The Nadia Raj and Malla Dynasty in Seventeenth-Century Bengal. Issue 2 (14th May 2014) - Wright, Samuel
<x content-type="archive" xml:space="preserve">Abstract</x> This paper examines the values that informed the actions of two polities in seventeenth-century Bengal, the Nadia Raj and the Malla dynasty, through a close analysis of their temple inscriptions—a form of royal laudation or praśasti. Focusing on this inscriptional record of each polity, the paper is divided into three sections. The first section analyzes the language of the inscriptions in order to examine the ways in which each polity crafts a political language. The second section addresses how each set of inscriptional records speaks to each polity's political culture. Finally, the third section discusses questions of patronage and reception in order to draw connections in each polity between its public language and its public settings. The paper concludes with some thoughts on what it meant for a polity to speak publicly in seventeenth-century Bengal.